Measuring digital readiness in resource-poor populations: A proposal - Steinke, Jonathan; Ortiz Crespo, Berta; Lasdun, Violet (2024)
Digital readiness refers to individuals’ ability to effectively engage with digital technologies. Digital development stakeholders, for example in the sectors of telehealth, e-government, or digital agriculture, need to understand digital readiness of their target groups to design effective interventions. Yet to date, there is no comprehensive quantitative tool for analyzing digital readiness at population level at low cost. Here, we propose a simple digital readiness score for rural populations in low- and middleincome countries. Calculating the score requires enumerating just ten dichotomous questions, covering four key dimensions: access to digital technologies, use of digital technologies, digital skills, and the enabling environment. To demonstrate the idea, we present data from 364 farmers in rural Tanzania and explore internal heterogeneity. In the future, similar digital readiness assessments could help with (i) identifying opportunities for digital interventions, (ii) targeting interventions to different groups within a population, and (iii) prioritizing design and investment decisions in digital development.